A critical investigation of the semantic and morphological aspects of terminological incompetence (with special reference to the English-speaking student of Physical Science and History in the Cape Education Department high school) - Venter, Malcolm Gordon (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1984)
From Background to the thesis: It has been said that 'educational failure is language failure'. It can be argued here that there are many other factors which could cause educational failure and that language failure does not necessarily result in lack of academic success. However, it is no doubt true that the schoolchild who does not attain a certain type of language competence will be handicapped as regards academic performance. The underlying reason for this is the fact that our educational system is heavily reliant on language - and espacially the written language - as a medium of learning as opposed to the 'direct learning' experiences advocated by certain educationists today such as Ivan Illich in America and John Holt in Britain. Language is the basis both of learning and of communicating what has been learnt. From the moment the child steps into his first period class in the morning till he leaves the last five hours later the child is involved in what is primarily a verbal experience.
Keywords: English language -- Semantics; English language -- Morphology